Aggressive International Tax Planning by Multinational Corporations: The Canadian Context and Possible Responses - Arnold, Brian J.; Wilson, James R. (Research Paper No. 29, 2014., 2014)
Aggressive international tax planning by multinational corporations has lately fallen under intense political scrutiny. U.S. politicians have called out some American multinationals, including Apple, Amazon, Starbucks and Google, for relocating profits abroad to avoid American taxes. More recently, politicians accused Burger King of being unpatriotic for its own purported “tax inversion” maneuver, in which it would acquire Canada’s Tim Hortons and shift the head office from Florida to Ontario, benefitting from the lower northern tax rates. The Chicago-based Walgreens pharmacy chain recently backed off a “tax inversion” plan to relocate to Switzerland (the former headquarters of Alliance Boots, a company acquired by Walgreens), apparently having assessed the political risk as too high. This sort of aggressive international tax planning by multinational corporations was what G20 members had committed to fighting against when they endorsed the OECD’s “action plan” against base erosion and profit shifting (BEPS). Canada has been vigilant about improving its tax framework to prevent non-resident corporations from eroding the Canadian tax base, having enacted thin-capitalization rules and, more recently, foreign-affiliate-dumping rules, as well as proposing anti-treaty-shopping measures. But despite Canada’s commitment to the OECD’s BEPS Action Plan, the Canadian government has been reluctant to follow through on implementing rules that might affect its own resident corporations and their international competitiveness. This is most notably visible in the generous participation exemption for dividends from foreign affiliates, the absence of rules restricting the deductibility of interest expenses incurred to earn exempt dividends from foreign affiliates. Canada may be reluctant to fully follow through on all aspects of the OECD’s BEPS Action Plan. As the examples of Apple, Amazon, Google and Starbucks demonstrate, the American government has so far been unable to bring itself to take any meaningful action against aggressive international planning by U.S.resident corporations. Were Canada to enact and enforce rules that clamped down on aggressive international tax planning by its own resident corporations, it would only put Canadian firms at a competitive disadvantage relative to American (or other international) rivals. Until the United States is willing and able to take the lead on aggressive international tax planning by multi-national corporations, the reality is that smaller countries, including Canada, should be cautious about making changes to its international tax rules that are dependent on other countries making similar changes.